2018
DOI: 10.3389/fgene.2018.00630
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Diversity and Phylogenetic Characteristics for High-Altitude Adaptive Kham Tibetan Revealed by DNATyperTM 19 Amplification System

Abstract: Tibetans residing in the high-altitude inhospitable environment have undergone significant natural selection of their genetic architecture. Recently, highly mutational autosomal short tandem repeats were widely used not only in the anthropology and population genetics to investigate the genetic structure and relationships, but also in the medical genetics to explore the pathogenesis of multiple genetic diseases and in the forensic science to identify individual and parentage relatedness. However, genetic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Ancient/modern genomes from the TP showed a clear connection with the northern modern Han Chinese and Neolithic-NEAs, especially with the coastal Houli people from Shandong, inland Yangshao and Longshan people from Henan, and Qijia people from Ganqing region, which supported the northern China origin of modern Tibeto-Burman-speaking populations. Shared ancestry revealed by our PCA, pairwise F ST and outgroup-f 3 -values, ADMIXTURE, and f 4 -statistics among ancient/modern highlanders and NEA lowlanders showed their close relationship, which was consistent with genetic similarities revealed by the forensic low-density genetic markers and uniparental haplotype/haplogroup data (Zou et al, 2018;Chen P. et al, 2019;He et al, 2019). Direct evidence supported and confirmed this proposed common origin of the Sino-Tibetan (North China origin hypothesis) that was provided by the phylogenetic relationship reconstruction.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Ancient/modern genomes from the TP showed a clear connection with the northern modern Han Chinese and Neolithic-NEAs, especially with the coastal Houli people from Shandong, inland Yangshao and Longshan people from Henan, and Qijia people from Ganqing region, which supported the northern China origin of modern Tibeto-Burman-speaking populations. Shared ancestry revealed by our PCA, pairwise F ST and outgroup-f 3 -values, ADMIXTURE, and f 4 -statistics among ancient/modern highlanders and NEA lowlanders showed their close relationship, which was consistent with genetic similarities revealed by the forensic low-density genetic markers and uniparental haplotype/haplogroup data (Zou et al, 2018;Chen P. et al, 2019;He et al, 2019). Direct evidence supported and confirmed this proposed common origin of the Sino-Tibetan (North China origin hypothesis) that was provided by the phylogenetic relationship reconstruction.…”
Section: Discussionsupporting
confidence: 86%
“…Contemporary Tibetans could trace their main ancestry back to the Neolithic millet farmers ( Li et al, 2019 ). Moreover, the genetic variations of modern Tibetan groups have also been explored based on the forensically available markers ( Wang Z. et al, 2018 ; Zou et al, 2018 ; He et al, 2019 ). However, the low resolution of these markers hindered the comprehensive understanding of prehistoric human activities on the TP and impeded the dissection of the ancestral component of Tibetans.…”
Section: Introductionmentioning
confidence: 99%
“…Linguistic study from the Bayesian phylogenetic analysis of the Sino-Tibetan language family has suggested that the Tibeto-Burman-speaking populations diverged from Han Chinese with an average coalescence age of approximately 5.9 kya ( Zhang et al, 2019 ). Furthermore, genetic observations based on forensically related markers also revealed the consistent phylogenetic relationships between Tibetan and other geographically or ethnically different groups ( He et al, 2018a , b ; Wang et al, 2018b , 2020 ; Zou et al, 2018 ; Li et al, 2019a ).…”
Section: Introductionmentioning
confidence: 81%
“…To gain insights into the genetic diversity and forensic characteristics of forensic Y-chromosomal genetic markers, we genotyped and analyzed 27 Y-STRs in 230 Shigatse Ü-Tsang Tibetans (SUT) and 172 Chamdo Kham Tibetans (CKT). Subsequently, we performed comprehensive population comparisons corresponding to cultural, geographical or linguistic groups to dissect the genetic similarities and differences between our studied Tibetan populations and Chinese reference populations or other adjacent Tibetan-Burman speaking populations 20,3542 .…”
Section: Introductionmentioning
confidence: 99%